A Comparative Analysis on the Strategy of Impression Management and Public Diplomacy of Two Indonesian Presidents at APEC CEO Summit - INRI INGGRIT INDRAYANI (Universitas Muhammadiyah Yogyakarta, 2016)
This research aims to analyze speeches of the former Indonesian President SusiloBambang Yudhoyono (SBY) and the current Indonesia President Joko Widodo(Jokowi) at the APEC CEO Summit. Jokowi gave his speech in Beijing, China in2014, while SBY delivered his speech in Bali in 2013. Both speeches have constructively examined as image management strategies to build an impressionmanagement at the APEC CEO Summit. APEC is one of crucial forum to buildinternational relationships, draw the investment opportunities from various countries and demonstrate their competencies as leaders. Therefore, it was important to analyze how both leaders presented themselves in front of the international public to build positive image and identity. This study used qualitative approach with content analysis as the method. This research incorporated taxonomy of Jones and Pittman which divided into five categories: Self-promotion, Ingratiation, Exemplification, Intimidation and Supplication. In regard to the data and related setting, this study had eliminated intimidation and supplication category. The findings showed that both SBY and Jokowi applied impression management in their public diplomacy in different ways. SBY applied self-promotion more frequently than Jokowi. SBY tended to display his image in formal and normative way as a systematic, charismatic and competent worldwide leader. Meanwhile, Jokowi displayed himself as a confident, straightforward and egalitarian as well as authoritative leader by using more aggressive, detailed and informal ways in order to gain foreign investment.